Enhancing Educational Equality: A Comprehensive Analysis of the Implementation and Impact of Restorative Justice Practices on Mitigating Racial Disparities in School Discipline Within Urban Public Schools in the United States - Alma Gil (Law and Economy, 2023)
This research explores the implementation and impact of restorative justice practices in addressing racial disparities in school discipline within U.S. urban public schools. The study delves into the challenges, successes, and recommendations for sustainable change in policy and practice. Theoretical frameworks and case studies are employed to analyze the influence of restorative justice on school climate, student well-being, and academic outcomes. Identified challenges include resource limitations, resistance to change, inadequate training models, and time constraints. Recommendations encompass policy adjustments, professional development initiatives, continuous evaluation, community partnerships, integration with mental health support, and addressing cultural sensitivity.